Assessment of non-ketotic hypoglycaemia in new born attending in Malda Medical College and Hospital - Dawn, Indranil; Jeauddin, Sk.; Biswas, Gauranga; Jana, Jadab Kumar (International Journal of Contemporary Pediatrics, 2017)
Background: Blood glucose level of <40/dl irrespective of period of gestation is known as hypoglycaemia. Nonketotic hypoglycaemia is associated with disorders of fructose or galactose metabolism, hyperinsulinism, fatty acid oxidation and GH deficiency. Aim of our study to detect the new born having clinical manifestations of hypoglycaemia, measure the capillary blood glucose and urinary ketone bodies in neonates with sign and symptoms of hypoglycaemia and to perform detail work up of neonates having non ketotic hypoglycaemia. Methods: It is hospital based cross-sectional study carried out for one calendar year extending from 01.01.2015 to 31.12.2015. Results: Thirty-five patients were identified as hypoglycemic Nine patients were diagnosed with non ketotic hypoglycemia for a prevalence of 8.5/100, 00. Two patients had the low growth hormone (GH) levels (0.4 ng/ml and 0.5 ng/ml). Three patients had increased Asparate Aminotransferase (AST) and Alanine Aminotransferase (ALT) level. Three patients increased urinary acetyl-carnitine level. Conclusions: Patient suffering from different congenital disorder and an extensive and overzealous workup for endocrinopathy or inborn error of metabolism is necessary.